Karakteristik Aerosol Optical Depth (AOD) di Cagar Biosfer Lore Lindu Berdasarkan Data Aeronet - Henri Panggabean; Sunardi Sunardi; Asep Firman Ilahi; Yuliana Susilowati (Buletin GAW Bariri (BGB), 2023)
The presence of aerosols in the air is an indicator of air quality. Aerosol observations have been carried out in the Lore Lindu National Park area using a Sunphotometer which produces AOD values at several wavelengths. This study uses AOD data at a wavelength of 500 nm Aronet Version 3 Level 2.0. The aerosol observations are incorporated in the Aerosol Robotic Network (Aeoronet). Monthly average rainfall data is obtained using an Ombrometer rainfall measurement in millimeters (mm). Analysis of the data on the average total AOD value obtained that the composition of the aerosol is dominated by fine particles (Fine Mode) and then coarse particles (coarse mode). The highest AOD value is at 6.00 at the lowest temperature and in October at the end of the dry season. The relationship between AOD 500nm and temperature has an inverse ratio. AOD with rainfall shows slightly different characteristics, where when there is high rainfall the AOD trend is still high but will change drastically for the next 3 months and vice versa if there is little rainfall then the AOD trend will start to rise for the next 3 months. Wind direction has no significant effect on the AOD and Angstrom Exponent values, but wind speed has an influence on the AOD and Angstrom Exponent values.